A hybrid coding retransmitted chipless tag loaded by microstrip resonator. (February 2019) - Ma, Zhonghua; Chen, Chih-Cheng
Abstract: Application of low-cost tag in radio frequency identification (RFID) system has promoted the development of internet of things (IoT). Chipless tag loaded by L-shaped microstrip resonator is proposed to decrease the cost of the tag in this paper. The tag is connected with two transceiving orthogonal ultra-wideband (UWB) circular monopole antennas. Chipless tag is constituted by L-shaped microstrip resonator of different lengths and 50 Ω characteristic impedance microstrip transmission line. 20-bit frequency position coding capacity is obtained on 4.80–10.93 GHz frequency band; 60-bit coding capacity could be obtained by hybrid coding with frequency position modulation and amplitude modulation. Tags of several typical coding with 4 bits coding capacity are measured and the results are basically the same as the simulation results.